Characterization Of Staphylococcin By Peptide Mass Ingerprinting - J.VIMALIN HENA,; S.S SUDHA, (International Journal of Pharma and Bio Sciences, 2011)
Protein components such as Staphylococcin, to characterize an emerging subgroup of bacteriocins, identified by MALDI –TOF were found to have activities in the single nanomolar range. Peptide mass finger printing is a protein identification technique in which mass spectrometer is used to measure the masses of proteolytic peptide fragments. The protein is then identified by matching the measured peptide masses to corresponding peptide masses from protein or nucleotide sequence database. Staphylococcins are bacteriocins produced by Staphylococci, which are gram positive bacteria with medical and veterinary importance. Most bacteriocins produced by Staphylococci are either lantibiotics (e.g. Pep 5, epidermin, epilancin k7, epicidin 280, Staphylococcin c55/Bac R1 and nukacin ISK-1) or class II bacteriocins (e.g. Aureocins A70 and 53). Only one Staphylococcin belonging to class III, lysostaphin, has been described so far. Production of Staphylococcins is a self protection mechanism that helps Staphylococci to survive in their natural habitats. However, since these substances generally have a broad spectrum of activity, inhibiting several human and animal pathogens, it can be used as an antimicrobial agent . The aim of this work was to study the effectiveness of staphylococcin isolated from MRSA against the MRSA strain. So that the staphylococcin can be used as an novel drug molecule.Methicillin resistant Staphylococcus aureus strain, which is a bacteriocin producer was isolated, purified by ammonium sulphate precipitation test and dialysis. Molecular weight was determined by using Tricine SDS-PAGE and its activity against MRSA was confirmed by agar well assay which paved way to analyse the peptide sequence by MALDI TOF which can be further used in combination with bioinformatic tools in a novel drug design